2022
DOI: 10.5455/ajvs.18032
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Pattern of E. coli Isolated from Various Animal Sources at El Behera Governorate

Abstract: The emergence of multidrug resistant E. coli isolated from animal and animal products become the main wary of food safety and public health authorities worldwide. The present study was undertaken to recognize the most important serovars and the antimicrobial sensitivity patterns of E. coli isolated from animals and animal products. Results showed that out of the 300 examined samples (75 cows mastitic milk, 77 buffalo's mastitic milk, 40 cattle meat, 43 buffaloes meat and 65 chicken meat), 60 isolates (20 %) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our results are in line with those reported in a previous study conducted in Italy by Grispoldi et al [ 52 ], who found that 89.7% of E. coli from bovine lymph nodes were resistant to cephalothin, which is recognized as an effective antimicrobial against Gram-negative as well as Gram-positive bacteria. Furthermore, a relatively lower resistance rate of 57% was observed in E. coli serovars isolated from bovine origin meat samples (four cows and three buffaloes) in Egypt against cephalothin [ 53 ]. Interestingly, despite the two third-generation cephalosporins, namely ceftriaxone and cefotaxime, being similar in their antibacterial spectrum, indications, and route of administration, the isolates examined showed a resistance rate of 29.4% against cefotaxime and a resistance rate of only 3.97% against ceftriaxone ( Table 2 ), which may be attributed to the difference in the administration dose and elimination half-life between the two antibiotics (ceftriaxone: 2 g once a day with half-life elimination of 8.8 h versus cefotaxime: 2 g every 4 h, 1.2 h) [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in line with those reported in a previous study conducted in Italy by Grispoldi et al [ 52 ], who found that 89.7% of E. coli from bovine lymph nodes were resistant to cephalothin, which is recognized as an effective antimicrobial against Gram-negative as well as Gram-positive bacteria. Furthermore, a relatively lower resistance rate of 57% was observed in E. coli serovars isolated from bovine origin meat samples (four cows and three buffaloes) in Egypt against cephalothin [ 53 ]. Interestingly, despite the two third-generation cephalosporins, namely ceftriaxone and cefotaxime, being similar in their antibacterial spectrum, indications, and route of administration, the isolates examined showed a resistance rate of 29.4% against cefotaxime and a resistance rate of only 3.97% against ceftriaxone ( Table 2 ), which may be attributed to the difference in the administration dose and elimination half-life between the two antibiotics (ceftriaxone: 2 g once a day with half-life elimination of 8.8 h versus cefotaxime: 2 g every 4 h, 1.2 h) [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%